Evaluasi Kemampuan Hidrolika Saluran Drainase Pondok Sidokare Indah terhadap Debit Banjir Rancangan Kala Ulang 2, 5, dan 10 Tahun - Falah Faustabi Akbar; Esti Wulandari; Dika Ayu Safitri (Pusat riset dan Inovasi Nasional, 2026)
Rapid population growth in Sidoarjo Regency has triggered massive land-use changes, resulting in increased surface runoff and reduced performance of the drainage system. This study aims to evaluate the hydraulic capacity of drainage channels in the Pondok Sidokare Indah Housing area against design flood discharges with return periods of 2, 5, and 10 years. The method used is a descriptive quantitative approach, involving hydrological analysis using maximum daily rainfall data from 2015–2025 and hydraulic modeling of the existing channel along 350 meters. The frequency analysis results indicate that the Log Pearson Type III distribution is the most suitable method based on statistical parameters and the Smirnov-Kolmogorov goodness-of-fit test. The calculation of design flood discharge using the rational method yields values of 0.749 m³/s (2-year), 1.003 m³/s (5-year), and 1.164 m³/s (10-year). Meanwhile, the maximum capacity of the existing channel ranges only between 0.534 m³/s and 0.733 m³/s. The comparison between hydrological load and channel capacity shows that all observation points (Sta 0+000 to Sta 0+350) are in overflow condition, even for the lowest return period flood discharge. This condition confirms that the current channel dimensions are no longer adequate and require normalization to mitigate annual flooding in the area.